Beyond language: The unspoken sensory-motor representation of the tongue in non-primates, non-human and human primates. (August 2022) - Bono, Davide; Belyk, Michel; Longo, Matthew R.; Dick, Frederic
Abstract: The English idiom " on the tip of my tongue " commonly acknowledges that something is known, but it cannot be immediately brought to mind. This phrase accurately describes sensorimotor functions of the tongue, which are fundamental for many tongue-related behaviors (e.g., speech), but often neglected by scientific research. Here, we review a wide range of studies conducted on non-primates, non-human and human primates with the aim of providing a comprehensive description of the cortical representation of the tongue's somatosensory inputs and motor outputs across different phylogenetic domains. First, we summarize how the properties of passive non-noxious mechanical stimuli are encoded in the putative somatosensory tongue area, which has a conserved location in the ventral portion of the somatosensory cortex across mammals. Second, we review how complex self-generated actions involving the tongue are represented in more anterior regions of the putative somato-motor tongue area. Finally, we describe multisensory response properties of the primate and non-primate tongue area by also defining how the cytoarchitecture of this area is affected by experience and deafferentation. Highlights: Ipsi- and contralateral passive stimuli delivered on the tongue of non-human primates are represented in separate fields. The cortical representation of the tongue in humans is cranial-nerve-dependent. Future research on lingual motor control should use paradigms that isolate tongue motion from related orofacial muscles. The tongue somato-motor representation is highly plastic in both primates and non-primates.